THE FACTORS OF INFLUENCE ON THE QUALITY OF TOURIST SERVICES IN THE REGION - Matviichuk, Liudmyla; Karpiuk, Iryna (Global Prosperity, 2021)
The article considers the main directions of the quality assurance of tourist services at the region's level. We proved that the qualitative development of tourist regions requires changes in the structure of production of a tourist product and significant changes in the organization of its production. The current state of services in the regions of Ukraine is under the impact of a significant number of factors. The main determinants are the "COVID-19" pandemic spread, increasing number of natural and anthropogenic disasters, the spread of terrorism and hostilities, et cetera. All these factors hinder the development of services. However, to promote domestic tourism as one of the areas of service in Ukraine, the pandemic was more resultative than joined industry reforms. Today, there is an increase in domestic tourists, and the tourism industry could get significant profits from the surge of domestic tourism. However, most of these trips are self-organized. In addition, most current tourists are looking for new experiences that allow relaxing, see and hear, and feel, taste, try, and learn about the area through cuisine, traditions, and ceremonies to take part in them. Therefore, we tried to substantiate new ways to improve the quality of service in the regions of Ukraine. The analysis of factors influencing the quality of regional tourist services is essential for the future development